Nurse liaison: a strategy for counter-referral - Ester do Nascimento Ribas; Elizabeth Bernardino; Liliana Muller Larocca; Paulo Poli Neto; Gisele Knop Aued; Camilla Pinheiro Cristaldi da Silva
ABSTRACT Objective: to identify the profile of the counter-referred patients by the "nurse liaison" and to describe the experience of the professionals who participated in the project. Method: intervention research, with twelve nursing nurses from a hospital and an Emergency Care Unit, and 26 nurses from Primary Health Care. Data were obtained through questionnaires and counter-referral forms. Results: Out of 43 counter-referred individuals, 62.8% are over sixty years, 53.5% are men with multi-pathologies. Among the positive aspects, the nurses highlighted the dialogue between health care services, agility in the acquisition of inputs for the continuity of care in primary care, benefiting patients after hospital discharge. The greatest challenge was the lack of time and the deficit of nurses to perform the function. Final considerations: the presence of the "nurse liaison" has proved to be an important strategy to improve integration between services and to promote continuity of care.